LAKON BANGSAWAN SUMATRA UTARA, TINJAUAN SINTAKTIKA - Suyadi Suyadi (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2019)
The performance of drama bangsawan not only carries social, economic, and political missions. The role of drama bangsawan is increasingly important and strategic in organizing the life of the nation, state, and society. In addition to playing a role to explore the cultural and artistic values that we have, royal drama can also play a role in encouraging the realization of complete human development, which also means not only teaching material/physical, but also very useful to order the mental and spiritual of every human being. This paper presents the syntactic aspects of the drama bangsawan in North Sumatra. The syntactic aspect which is part of Charles Morris's semiotic theory explores the nature and pattern of stories of aristocratic plays. This review succeeded in discovering the existence of the aristocratic theater in North Sumatra and its shape patterns. This folk theater originally took place among the aristocrats in the Serdang Sultanate and eventually became the property of most people. The aristocratic form or concept of the show was maintained even though it was no longer played at the Palace, as the palaces in the former North Sumatra Residency after the Social Revolution collapsed. This theater should be inherited as a non-fine cultural form belonging to North Sumatra.